Genotype and haplotype analysis of TP53 gene and the risk of pancreatic cancer: an association study in the Czech Republic - Naccarati, A; Pardini, B; Polakova, V; Smerhovsky, Z; Vodickova, L; Soucek, P; Vrana, D; Holcatova, I; Ryska, M; Vodicka, P (Carcinogenesis, 2010)
Pancreatic carcinoma is the fourth leading cause of cancer-related deaths in the Czech Republic, with only a minimum of patients surviving 5 years. The aetiology and molecular pathogenesis are still weakly understood. TP53 has a fundamental role in cell cycle and apoptosis and is frequently mutated in solid tumours, including pancreatic cancer. Based on the assumption that genetic variation may affect susceptibility to cancer development, the role of TP53 polymorphisms in modulating the risk of pancreatic cancer may be of major importance. We investigated four selected polymorphisms in TP53 (rs17878362:A(1)>A(2), rs1042522:G>C, rs12947788:C>T and rs17884306:G>A) in association with pancreatic cancer risk in a case-control study, including 240 cases and controls (for a total of 1827 individuals) from the Czech Republic. Carriers of the variant C allele of rs1042522 polymorphism were at an increased risk of pancreatic cancer [odds ratio (OR) 1.73; 95% confidence interval (CI) 1.26-2.39; P = 0.001]. Haplotype analysis showed that in comparison with the most common haplotype (A(1)GCG), the A(2)CCG haplotype was associated with an increased risk (OR 1.39; 95% CI 1.02-1.88; P = 0.034) and the A(1)CCG with a reduced risk (OR 0.30; 95% CI 0.12-0.76; P = 0.011) for this cancer. These results reflect previous findings of a recent association study, where haplotypes constructed on the same TP53 variants were associated with colorectal cancer risk [Polakova et al. (2009) Genotype and haplotype analysis of cell cycle genes in sporadic colorectal cancer in the Czech Republic. Hum. Mutat., 30, 661-668.]. Genetic variation in TP53 may contribute, alone or in concert with other risk factors, to modify the inherited susceptibility to pancreatic cancer, as well as to other gastrointestinal cancers.
Keywords: senioři; Genetic Predisposition to Disease; senioři nad 80 let; genotyp; Genotype; Česká republika; Middle Aged; Haplotypes; mužské pohlaví; nádory slinivky břišní; Adult; Czech Republic; Aged, 80 and over; ženské pohlaví; Humans; Pancreatic Neoplasms; haplotypy; lidé středního věku; Genes, p53; Risk; riziko; dospělí; genetická predispozice k nemoci; Female; Aged; geny p53; lidé; Male